Changes in calcium-dependent protein kinase activity during in vitro tuberization in potato - MacIntosh, G.C. (1996)
A soluble Ca2+-dependent protein kinase (CDPK) was purified to homogeneity in potato (Solanum tuberosum L.) plants. Potato CDPK was strictly dependent on Ca2+ (one-half maximal activation 0.6 μM) and phosphorylated a wide diversity of substrates, in which Syntide 2 was the best phosphate acceptor (Michaelis constant = 30 μM). The kinase was inhibited by Ca2+- chelating agents, phenotiazine derivatives, and N-(6-aminohexyl)-5-chloro-1- naphthalenesulfonamide (one-half maximal inhibition = 0.25 mM). Polyclonal antibodies directed against the regulatory region of the soybean CDPK recognized a 53-kD polypeptide. In an autophosphorylation assay, this same band was strongly labeled with [γ-32P]ATP in the presence of Ca2+. CDPK activity was high in nontuberized plants, but increased 2.5-fold at the onset of tuber development and was reduced to one-half of its original activity when the tuber had completed formation. In the early stages of tuberization, Ca2+-dependent phosphorylation of endogenous targets (specific bands of 68, 51, and 46 kD) was observed. These polypeptides were not labeled in nontuberizing plants or in completely formed tubers, indicating that this phosphorylation is a stage-specific event. In addition, dephosphorylation of specific polypeptides was detected in tuberizing plants, suggesting the involvement of a phosphatase. Preincubation of crude extracts with phosphatase inhibitors rendered a 100% increase in CDPK activity.